2008
DOI: 10.2967/jnumed.107.050138
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Relationship Between Coronary Microvascular Dysfunction and Delayed Contrast Enhancement in Patients with Hypertrophic Cardiomyopathy

Abstract: To clarify the spatial relationship between coronary microvascular dysfunction and myocardial fibrosis in hypertrophic cardiomyopathy (HCM), we compared the measurement of hyperemic myocardial blood flow (hMBF) by PET with the extent of delayed contrast enhancement (DCE) detected by MRI. Methods: In 34 patients with HCM, PET was performed using 13 N-labeled ammonia during hyperemia induced by intravenous dipyridamole. DCE and systolic thickening were assessed by MRI. Left ventricular myocardial segments were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 38 publications
8
52
0
Order By: Relevance
“…The distribution of fi brosis was atypical for CAD and predominated in the midwall and subepicardial portions of the LV walls, encompassing multiple coronary territories. This pattern was compatible with myocardial fi brosis associated with myocardial ischemia secondary to microvascular derangement and chronic myocarditis, as also documented in hypertrophic and dilated cardiomyopathy 55,56 . Similar fi ndings and interpretation were reported by another study, which investigated 67 Chagas disease patients.…”
Section: Coronary Microvascular Dysfunctionmentioning
confidence: 54%
“…The distribution of fi brosis was atypical for CAD and predominated in the midwall and subepicardial portions of the LV walls, encompassing multiple coronary territories. This pattern was compatible with myocardial fi brosis associated with myocardial ischemia secondary to microvascular derangement and chronic myocarditis, as also documented in hypertrophic and dilated cardiomyopathy 55,56 . Similar fi ndings and interpretation were reported by another study, which investigated 67 Chagas disease patients.…”
Section: Coronary Microvascular Dysfunctionmentioning
confidence: 54%
“…15 In HCM, the intramural coronary arteries exhibit thickened walls and narrowed lumens, 98 resulting in myocardial ischemia. 14,[62][63][64] With progression of disease, there is even an indication that the endocardial vasculature can develop into a highly interconnected vascular plexus communicating with the ventricular cavity as an adaptation to severe chronic ischemia. 99 There is also a body of emerging evidence that in HCM, resting and dynamic geometric abnormalities exist in the mitral valve.…”
Section: Organ-level Physiologymentioning
confidence: 99%
“…59 Thus, neurohormonal antagonism using the above, natriuretic peptide mimetics, or even modulation of G protein-coupled receptor kinases (GRKs) that desensitize ␤ARs, 60 represent candidates for HCM therapy. Neurohormonal antagonism potentially has pleiotropic benefits including suppression of: tissue/systemic neuroendocrine activation, electrolyte defects (Kϩ and Mg 2ϩ ), fibroblast activity with collagen deposition (eg, via BMP-7/TGF-␤1) 15,61 and mitigation of microvasculopathy, 14,62 which may have pathophysiological 63 and prognostic 64 -66 benefits in HCM. In mouse, feline, and human studies, RAAS inhibition in HCM using ACE-I/ARBs/spironolactone, diminished mi- Figure 2.…”
Section: Signalingmentioning
confidence: 99%
“…47,77, 78 Approximately 70% of HCM patients have evidence of LGE on CMR. 79, 80 Olivotto et al found substantial amounts of LGE in a subset of patients with HCM and low-normal EF values (50-65%) in comparison with patients with higher EF, 81 but little or no association was found between EF and several standard clinical and demographic parameters, such as age, sex, LV cavity dimensions, wall thickness or LVM.…”
Section: Myocardial Fibrosis In Primary Lvhmentioning
confidence: 99%